Effectiveness of a return-to-work intervention for subacute low-back pain - Hlobil, Hynek; Staal, J Bart; Spoelstra, Maaike; Ariëns, Geertje AM; Smid, Tjabe; van Mechelen, Willem (Scandinavian Journal of Work, Environment & Health, 2005)
The effectiveness of return-to-work intervention for subacute low-back pain on work absenteeism, pain severity, and functional status was examined by means of a systematic review of randomized controlled trials. Publications in English that met the selection criteria were identified in a computer-aided search and assessed for methodological quality. A best-evidence synthesis was performed instead of statistical data pooling, because of the heterogeneity of the interventions and study populations. Five of nine studies comparing return-to-work intervention with usual care were identified as methodologically high-quality studies. Strong evidence was found for the effectiveness of return to work intervention on the return-to-work rate after 6 months and for the effectiveness of return-to-work intervention on the reduction of days of absence from work after ≥12 months. It can be concluded that return-to-work interventions are equal or more effective regarding absence from work due to subacute low-back pain than usual care is.
Keywords: back injury; behavioral treatment; effectiveness; ergonomic measure; health education; intervention; low-back pain; occupational health care; pain severity; physical exercise; rehabilitation; return to work; review; subacute low-back pain; work absenteeism